Pelatihan Pemanfaatan Buah Mangrove Menjadi Produk Pangan Bagi Masyarakat - Dewi Wahyuni Baderan; Weny JA Musa (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
Mangroves are ecosystems in coastal areas that have important ecological and economic benefits derived from leaves, seeds and fruit. One of the coastal areas that contains mangrove forests is Bajo Village, Tilamuta District, Bualemo Regency, Gorontalo Province which is included in the Tomini Bay marine area which is the heart of the socio-economic life of the local community. Not many coastal communities know that mangroves contain nutrients including carbohydrates, proteins, and antioxidants that are important for humans, which are sourced from fruit and mangrove propagules and can be developed into raw materials for several foods that contain nutrients for human health. The specific target to be achieved is to provide knowledge/technology about diversification of non-rice food ingredients to coastal communities, especially those in the coastal area of Bajo Village, Tilamuta District, Bualemo Regency, Gorontalo Province in order to produce various products as an effort to improve the family economy. The methods to be used are group discussion, lecture, participatory, and exercise methods. If this group of women fishermen is skilled at processing mangrove fruit and marketing it, it is expected to increase the independence, quality of life, and family income of coastal women. In the long term, it becomes a mangrove-based livelihood system that supports the income of the Bajo coastal population. Mangrove-based livelihood systems require sustainable mangrove raw materials, this is an incentive for women to plant mangroves and preserve them. Thus, this activity empowers women fishermen to have equal access to mangrove conservation, and reduces carbon emissions in order to overcome global warming and climate change and to overcome food shortages in the future.